PSYCHOLOGICAL AND PHILOSOPHICAL FOUNDATIONS IN STRENGTHENING THE PANCASILA STUDENT PROFILE: IMPLEMENTATION IN MADRASAH IBTIDAIYAH - Nyai Raodotul Janah; Akhmad Affandi (PT Altin Riset Publishing, 2026)
This article examines the psychological and philosophical foundations embedded in the implementation of the Pancasila Student Profile within the Merdeka Curriculum, with a particular focus on Madrasah Ibtidaiyah in Indonesia. Using a qualitative descriptive approach, the study explores how educational psychology particularly the theories of Piaget and Vygotsky and educational philosophy, such as humanism and reconstructionism, inform student-centered learning, value internalization, and character formation. The findings reveal that project-based learning anchored in these foundations supports cognitive, affective, and moral development, aligned with the six dimensions of the Pancasila Student Profile. Furthermore, the article identifies contextual adaptation through religious and local values that reinforce the concept of